Protein S as an in vivo cofactor to activated protein C in prevention of microarterial thrombosis in rabbits. - Arnljots, B; Dahlbäck, B (The Journal of Clinical Investigation, 1995)
The antithrombotic effects of bovine activated protein C (APC) and protein S were investigated in a rabbit model of microarterial thrombosis. Because of the species specificity of the APC-protein S interaction, bovine APC expresses potent anticoagulant activity in rabbit plasma only when bovine protein S is also present. This provided a way to assess the contribution of bovine protein S to the antithrombotic effect of bovine APC. Rabbits were infused with boluses of activated protein C (0.1, 0.2, 0.4, or 0.8 mg/kg), protein S (0.5 mg/kg), or activated protein C (0.1 or 0.01 mg/kg) plus protein S (0.5 mg/kg). APC alone produced a dose-dependent antithrombotic effect, but only the group receiving the highest dose differed significantly from controls. While a low dose of activated protein C (0.1 mg/kg) alone had no antithrombotic effect, together with protein S (0.5 mg/kg) it produced a potent response. The presented results demonstrate the in vivo significance of protein S as a cofactor to activated protein C. The data show that a potent antithrombotic effect, without hemorrhagic side effects or significant systemic anticoagulation, may be achieved by low doses of activated protein C when combined with protein S. Images